Human ecology - Konstańczak, Stefan (Studia Ecologiae et Bioethicae, 2006)
Environmental problems do have a universal dimension: they concern entire humanity as well as each human being individually, therefore, a new ecology needs to be developed in which man will play a principal role being a focal point of the study, its creator and executor of its assumptions, the discipline thus understood is one of the aspects of general ecology for it studies relationships between man as a species and its environment, the author believes that, regardless of the standpoint that representatives of various sciences may take, the future of our species depends on the interdisciplinary approach toward the questions that are subject to human ecology studies.